Strict Liability in Indonesian and Dutch Environmental Civil Law: A Comparative Study - Rania Syifa Busroni; Citraresmi Widoretno Putri (JURNAL USM LAW REVIEW, 2025)
This study examines the application and characteristics of the strict liability principle in Indonesian and Dutch environmental civil law as a legal mechanism for environmental damage compensation. The research is motivated by differing normative approaches, where Indonesia adopts strict liability as a specific regime under environmental legislation, while the Netherlands develops it within general civil law through a risk-based liability framework. This study employs a normative juridical method using statutory, conceptual, and comparative law approaches by analyzing legislation, legal doctrines, and judicial practices in both jurisdictions. The findings reveal that the implementation of strict liability in Indonesia remains constrained by evidentiary challenges, particularly regarding causation and the scope of liability, whereas the Dutch system consistently applies risk-based liability without requiring proof of fault. The novelty of this research lies in its comparative assessment, positioning the Dutch model as a normative reference for strengthening the effectiveness of strict liability in Indonesia, especially in ensuring environmental restoration and the protection of affected communities. This study recommends reinforcing Indonesia’s strict liability framework through doctrinal harmonization, simplified evidentiary standards, and clearer environmental compensation mechanisms.